Addressing Maternal Healthcare through Demand Side Financial Incentives : Experience of Janani Suraksha Yojana Program in India - Gopalan, Saji S.; Varatharajan, Durairaj (BioMed Central, 2015)
Demand side financing (DSF) is a widely employed strategy to enhance utilization of healthcare. The impact of DSF on health care seeking in general and that of maternal care in particular is already known. Yet, its effect on financial access to care, out-of-pocket spending (OOPS) and provider motivations is not considerably established. Without such evidence, DSFs may not be recommendable to build up any sustainable healthcare delivery approach. This study explores the above aspects on India’s Janani Suraksha Yojana (JSY) program.